meso-2,2,2′,2′-Tetrachloro-1,1′-diphenyl-1,1′- bicyclopropyl and meso-2,2,2′,2′-Tetrabromo-1,1′-diphenyl-1,1′- bicyclopropyl - Lam, Y.-L. (2014)
Acta Crystallographica Section C: Crystal Structure Communications